The Bidirectional Relationship Between Obstructive Sleep Apnea and Metabolic Disease - Framnes, Sarah N.; Arble, Deanna M. (Frontiers in Endocrinology, 2018)
Obstructive sleep apnea (OSA) is a common sleep disorder, effecting 17% of the total population and 40-70% of the obese population. Multiple studies have identified OSA as a critical risk factor for the development of obesity, diabetes, and cardiovascular diseases. Moreover, emerging evidence indicates that metabolic disorders can exacerbate OSA, creating a bidirectional relationship between OSA and metabolic physiology. In this review, we explore the relationship between glycemic control, insulin, and leptin as both contributing factors and products of OSA. We conclude that while insulin and leptin action may contribute to the development of OSA, further research is required to determine the mechanistic actions and relative contributions independent of body weight. In addition to increasing our understanding of the etiology, further research into the physiological mechanisms underlying OSA can lead to the development of improved treatment options for individuals with OSA.